DESAIN BUKU PSIKOLOGI WARNA - WALDI RASYID, Drs. Muzni Ramanto, Dra. Lisa Widiarti, M.Sn (DEKAVE : Jurnal Desain Komunikasi Visual, 2014)
This thesis aims to produce a design that is attractive about the book Psychology of Color in Visual Communication media written by Muzni Ramanto. The design method used by the authors is the beginning of the data collection method is through observation, interviews, and documentation studies. Then proceed with the data analysis method using 5W +1 H analysis (what, where, when, who, why, and how) and creative approach. In this design the author will display the layout, cover, typography, and color in accordance with the contents of the book by using the software Corelldraw kalaborasi Grapics Suite X4 and Photoshop CS4. In addition, there are also test conducted on the design of consumer products Colour Design this book.Keywords: Design, Psychology, Book